Hubungan Pengetahuan Pus Tentang Alat Kontrasepsi Mow Dengan Minat PUS Terhadap Alat Kontrasepsi MOW di Praktek Bidan Hj. R Batubara Kota Padangsidimpuan - Siregar, Rya Anastasya (Universitas Aufa Royhan, 2019)
Women's Surgical Medical Contraception (MOW) is a method of permanent contraception in women, performed with a small operation to tie / clamp / cut the fallopian tubes. The purpose of this study was to determine the relationship between the level of EFA knowledge about MOW with EFA interest in MOW contraceptives. This research uses descriptive analytic method with cross sectional research design. The sampling technique uses accidental sampling with a total sample of 46 EFAs. Data were collected using a questionnaire. The analysis used is univariate analysis and bivariate analysis with chi-square statistical test with confidence level (95% CI) and α = 0.05. The results of this study indicate a significant relationship between EFA knowledge about MOW with EFA interest in contraception MOW (Pvalue = 0.007 <2 count = 9,807α = 0.05) and (> 2 table = 5.991). The conclusion is that there is a relationship between EFA knowledge about MOW with EFA interest in contraception MOW practice of midwife Hj. R. Coal of the city of Padangsidimpuan in 2018. Thus the authors propose a number of suggestions, namely for respondents to be able to increase knowledge and add insight about MOW contraception by asking health workers, reading books, watching television and so on so that EFA know about MOW contraception.